Role of attractiveness factors of the OECD countries in immigration - Kristina Duvnjak; Sinisa Bogdan; Suzana Baresa (UTMS Journal of Economics, 2017)
An influx of immigrants to developed countries, is an ongoing process that lasts for centuries. Numerous researches have been written encouraged by this topic. Today's free labor market enables immigrants to become a very influential aspect of every economy. With general stagnation and aging of word population, especially European, a question about level of immigration impact on active labor market appears. This paper is testing the stated, what are the factors that attract immigrants in OECD countries. Considering the main factors that encourage immigrants to migrate in specific country, this paper is testing how total GDP per country, as an indicator of level of economic growth, and social spending, as an indicator of support to those who need it, influence on their decision. The determined variable is asylum seeker as it is much precise in stating the thesis. The cross-section model which is used with 2015 data shows significant results.
Keywords: J23; J61; G01; 330; active labor market; asylum seekers; social spending; cross-section